2012
DOI: 10.1259/bjr/32938996
|View full text |Cite
|
Sign up to set email alerts
|

Towards clinical assessment of velopharyngeal closure using MRI: evaluation of real-time MRI sequences at 1.5 and 3 T

Abstract: Objective: The objective of this study was to demonstrate soft palate MRI at 1.5 and 3 T with high temporal resolution on clinical scanners. Methods: Six volunteers were imaged while speaking, using both four real-time steady-state free-precession (SSFP) sequences at 3 T and four balanced SSFP (bSSFP) at 1.5 T. Temporal resolution was 9-20 frames s 21 (fps), spatial resolution 1.661.6610.0-2.762.7610.0 mm 3 . Simultaneous audio was recorded. Signal-to-noise ratio (SNR), palate thickness and image quality score… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
45
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 47 publications
(82 reference statements)
1
45
0
Order By: Relevance
“…85 Few groups have proposed regional metrics that characterize SNR in upper airway regions of interest at several undersampling factors. 41,60,86 A controlled task-specific based RT-MRI experimentation was proposed to evaluate the temporal finite difference constraint along with median filtering; 87 the spatiotemporal fidelity of the reconstructions were evaluated on a mechanical motion phantom that consisted of water filled tubes rotating at predefined angular velocities. However, such a rotating phantom may not be optimal for other regularizers such as those involving low rank constraints.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…85 Few groups have proposed regional metrics that characterize SNR in upper airway regions of interest at several undersampling factors. 41,60,86 A controlled task-specific based RT-MRI experimentation was proposed to evaluate the temporal finite difference constraint along with median filtering; 87 the spatiotemporal fidelity of the reconstructions were evaluated on a mechanical motion phantom that consisted of water filled tubes rotating at predefined angular velocities. However, such a rotating phantom may not be optimal for other regularizers such as those involving low rank constraints.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past decade, a number of technical advancements in acquisition strategies, coil geometry design, reconstruction and artifact correction schemes have emerged, thereby providing a wide range of solutions to RT-MRI tradeoffs. 1,6,[39][40][41][42][43][44][45][46][47] This article focuses on the technical considerations relevant to implementing an RT-MRI protocol for upper airway imaging. This article is motivated by an outcome of the Speech MRI Summit meeting (Los Angeles, February 2014, endorsed by the ISMRM), where the speech MRI research community convened and agreed that there was an unmet need for a recommendations document for RT-MRI of speech.…”
mentioning
confidence: 99%
“…[16][17][18][19] The quest for improving the possible spatial and temporal resolution, and identifying effective trade offs for given application needs, is ongoing. However, with current imaging and audio acquisition capabilities, it is possible to collect large amounts of speech production data than ever before such as demonstrated by the current database.…”
Section: Discussionmentioning
confidence: 99%
“…On-thefly schemes are referred to those that allow for immediate visualization of the reconstructed images (with latency less than 500 ms), whereas off-line schemes are referred to those where the reconstructions are implemented off-line. Scott et al (20) utilized on-the-fly imaging with Cartesian trajectories and demonstrated temporal resolutions between 111 and 50 ms at spatial resolution of 1.6-2.7 mm 2 for velopharyngeal closure. Other investigators (1,21,22) utilized short spiral readouts to acquire images at a native time resolution of 54-78 ms, and a spatial resolution of 3.0-2.4 mm 2 , and visualize at 24 frames/sec using view sharing.…”
Section: Introductionmentioning
confidence: 99%